Éthique et pédagogie : entre l’institution de moralité et le désengagement éthique, comment ouvrir le champ d’un perfectionnement moral à l’école ? - Didier Moreau (Recherches en Éducation)
The new teaching of morality in school arouses a debate against metaphysical positions. This paper realizes a critical review of them, from their epistemological presuppositions, to propose a way of ethical training of oneself, according to the stoic practice of the spiritual exercises as far as possible of any transcendence. It is possible, in school, to conduce pedagogical practices opening the way of self ethical construction, by the share of values and experiencing. These practices are opened and turned to the horizon of improvement, because they are not subordinate to an institution of salvation which detains the Truth.